Effects of acupuncture synchronized rehabilitation therapy on upper limb motor and sensory function after stroke: a study protocol for a single-center, 2 × 2 factorial design, randomized controlled trial - Yu, Zifu; Yang, Xiaoxia; Qin, Fang; Ma, Tiantian; Zhang, Jie; Leng, Xiaoxuan; Bi, Hongyan; Liu, Xihua (Frontiers in Neurology, 2023)
Background Upper limb function reconstruction has been an important issue in the field of stroke rehabilitation. Due to the complexity of upper extremity dysfunction in stroke patients, the clinical efficacy produced by central or peripheral stimulation alone is limited. For this reason, our group has proposed acupuncture synchronized rehabilitation therapy (ASRT), i.e., simultaneous scalp acupuncture and intradermal acupuncture during rehabilitation. Pre-experiments results showed that this therapy can effectively improve the motor and sensory functions of upper limbs in post-stroke patients, but the clinical efficacy and safety of ASRT need to be further verified, and whether there is a synergistic effect between scalp acupuncture and intradermal acupuncture also needs to be studied in depth. Therefore, we designed a randomized controlled trial to compare the efficacy and safety of different therapies to explore a more scientific “synchronous treatment model.” Methods This is a single-center, randomized controlled trial using a 2 × 2 factorial design. We will recruit 136 stroke survivors with upper extremity dysfunction and randomize them into four groups (n = 34). All subjects will undergo routine treatment, based on which the Experimental Group 1: rehabilitation training synchronized with intradermal acupuncture treatment of the affected upper limb; Experimental Group 2: rehabilitation training of the affected upper limb synchronized with focal-side scalp acupuncture treatment, and Experimental Group 3: rehabilitation training synchronized with intradermal acupuncture treatment of the affected upper limb synchronized with focal-side scalp acupuncture treatment; Control Group: rehabilitation training of the affected upper limb only. The intervention will last for 4 weeks, 5 times a week. Both acupuncture treatments will be performed according to the Revised Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA). The primary outcome indicators for this trial are Fugl-Meyer Assessment-Upper Extremity and Somatosensory Evoked Potential. Secondary outcome indicators include Wolf Motor Function Test, Upper Extremity Function Test, revised Nottingham Sensory Assessment Scale, Diffusion Tensor Imaging, and Modified Barthel Index. The incidence of adverse events will be used as the indicator of safety. Discussion The study will provide high-quality clinical evidence on whether ASRT improves upper limb motor and sensory function and activities of daily living (ADL) in stroke patients, and determine whether scalp acupuncture and intradermal acupuncture have synergistic effects. Clinical trial registration https://www.chictr.org.cn/, Chinese Clinical Trial Registry [ChiCTR2200066646].